Love Island, Social Media, and Sousveillance: New Pathways of Challenging Realism in Reality TV - L'Hoiry, Xavier (Frontiers in Sociology, 2019)
This paper explores the changing nature of audience participation and active viewership in the context of Reality TV. Thanks to the ongoing rise of social media, fans of popular entertainment programmes continue to be engaged in new and innovative ways across a number of platforms as part of an ever-expanding interactive economy. Love Island 2018 has pushed the boundaries of this participatory culture by exploiting new forms of digital media in order to encourage multi-platform consumption of content by the show's fans. This paper argues that while this strategy has enabled Love Island to successfully exploit monetization opportunities, it has simultaneously created opportunities for the show's audience to group together online and form communities of resistance which have placed themselves in opposition to the show's producers. These fan communities have harnessed the connective powers of social media to pool together their means and knowledge and to eventually exercise modes of sousveillance designed to hold “powerful” actors to account for perceived wrongdoing on the show. Examples of such behavior during Love Island 2018 hint at a paradigm shift in the relationship between television producers and audiences and demonstrate the new pathways available to audiences as they seek to answer the perennial question of this entertainment genre: how real is Reality TV?